Norfloxacin—Toxicity for Zebrafish (Danio rerio) Focused on Oxidative Stress Parameters. (13th March 2014) - Bartoskova, Marta; Dobsikova, Radka; Stancova, Vlasta; Pana, Ondrej; Zivna, Dana; Plhalova, Lucie; Blahova, Jana; Marsalek, Petr
Abstract : The aim of the study was to investigate the effects of subchronic exposure of zebrafish ( Danio rerio ) to a fluoroquinolone norfloxacin, using selected oxidative stress parameters as a target. Toxicity tests were performed on zebrafish according to the OECD Guidelines number 203 and number 215. In the Subchronic Toxicity Test, a significant (P < 0.01 ) increase in the activity of glutathione peroxidase, glutathione S-transferase, and catalase was found. In the test, norfloxacin did not affect lipid peroxidation and catalytic activity of glutathione reductase. From the results, we can conclude that norfloxacin has a negative impact on specific biochemical processes connected with the production of reactive oxygen species in fish tested.